Is Pluto a Planet? : A Historical Journey through the Solar System - Weintraub, David A. (David Andrew), 1958- (Book collections on Project MUSE., 2007)
A Note from the Author: On August 24, 2006, at the 26th General Assembly of the International Astronomical Union (IAU) in Prague, by a majority vote of only the 424 members present, the IAU (an organization of over 10,000 members) passed a resolution defining planet in such a way as to exclude Pluto and established a new class of objects in the solar system to be called ""dwarf planets, "" which was deliberately designed to include Pluto. With the discovery of Eris (2003 UB313)--an outer solar system object thought to be both slightly larger than Pluto and twice as far from the Sun--astrono.